Inhibition of the Anti-Apoptotic Bcl-2 Family by BH3 Mimetics Sensitize the Mitochondrial Permeability Transition Pore Through Bax and Bak - Patel, Pooja; Mendoza, Arielys; Robichaux, Dexter J.; Wang, Meng C.; Wehrens, Xander H. T.; Karch, Jason (Frontiers in Cell and Developmental Biology, 2021)
Mitochondrial permeability transition pore (MPTP)-dependent necrosis contributes to numerous pathologies in the heart, brain, and skeletal muscle. The MPTP is a non-selective pore in the inner mitochondrial membrane that is triggered by high levels of matrix Ca2+, and sustained opening leads to mitochondrial dysfunction. Although the MPTP is defined by an increase in inner mitochondrial membrane permeability, the expression of pro-apoptotic Bcl-2 family members, Bax and Bak localized to the outer mitochondrial membrane, is required for MPTP-dependent mitochondrial dysfunction and subsequent necrotic cell death. Contrary to the role of Bax and Bak in apoptosis, which is dependent on their oligomerization, MPTP-dependent necrosis does not require oligomerization as monomeric/inactive forms of Bax and Bak can facilitate mitochondrial dysfunction. However, the relationship between Bax and Bak activation/oligomerization and MPTP sensitization remains to be explored. Here, we use a combination of in vitro and ex vivo approaches to determine the role of the anti-apoptotic Bcl-2 family members, which regulate Bax/Bak activity, in necrotic cell death and MPTP sensitivity. To study the role of each predominantly expressed anti-apoptotic Bcl-2 family member (i.e., Mcl-1, Bcl-2, and Bcl-xL) in MPTP regulation, we utilize various BH3 mimetics that specifically bind to and inhibit each family member. We determined that the inhibition of each anti-apoptotic Bcl-2 family lowers mitochondrial calcium retention capacity and sensitizes MPTP opening. Furthermore, the inhibition of each Bcl-2 family member exacerbates both apoptotic and necrotic cell death in vitro in a Bax/Bak-dependent manner. Our findings suggests that mitochondrial Ca2+ retention capacity and MPTP sensitivity is influenced by Bax/Bak activation/oligomerization on the outer mitochondrial membrane, providing further evidence of the crosstalk between the apoptotic and necrotic cell death pathways.